2018
DOI: 10.3389/fgene.2018.00107
|View full text |Cite
|
Sign up to set email alerts
|

Little Divergence Among Mitochondrial Lineages of Prochilodus (Teleostei, Characiformes)

Abstract: Evidence that migration prevents population structure among Neotropical characiform fishes has been reported recently but the effects upon species diversification remain unclear. Migratory species of Prochilodus have complex species boundaries and intrincate taxonomy representing a good model to address such questions. Here, we analyzed 147 specimens through barcode sequences covering all species of Prochilodus across a broad geographic area of South America. Species delimitation and population genetic methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 58 publications
8
27
1
Order By: Relevance
“…The maximum likelihood results of the GMYC model performed with COI was significantly higher (L = 696.0997) than that of the null model (L0 = 642.3439), allowing us to reject the hypothesis that all individuals belong to the same molecular unit. The GMYC single threshold analysis revealed the occurrence of three MOTUs within the Amazon River basin (Fig 2), increasing the number of MOTUs reported in previous studies [15,16] in this large basin. Our study recovered the previous Western and Eastern Amazon MOTUs (showed, respectively, in blue and green clusters in Fig 2) and raised an additional one, named hereafter Tapajós MOTU (orange cluster in Fig 2).…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…The maximum likelihood results of the GMYC model performed with COI was significantly higher (L = 696.0997) than that of the null model (L0 = 642.3439), allowing us to reject the hypothesis that all individuals belong to the same molecular unit. The GMYC single threshold analysis revealed the occurrence of three MOTUs within the Amazon River basin (Fig 2), increasing the number of MOTUs reported in previous studies [15,16] in this large basin. Our study recovered the previous Western and Eastern Amazon MOTUs (showed, respectively, in blue and green clusters in Fig 2) and raised an additional one, named hereafter Tapajós MOTU (orange cluster in Fig 2).…”
Section: Resultsmentioning
confidence: 54%
“…Ten samples were obtained from the Xingu (1) and Tocantins-Araguaia (9) drainages (Fig 1, Table 1). Additionally, we retrieved 48 sequences of P. nigricans and some congeneric nominal species from previous studies [15,16,[30][31][32], available at Genbank and Barcode of Life Data Base (BOLD Systems, https://www.boldsystems.org/index.php/databases) public databases (S1 Table). https://doi.org/10.1371/journal.pone.0237916.g001…”
Section: Biological Sampling and Ethical Requirementsmentioning
confidence: 99%
See 2 more Smart Citations
“…in the Jequitinhonha, 370 without any success, and this species was only documented in 2009 by an environmental report 371 based on traditional sampling and morphological identification (Kullander & Lucena, 2006;372 Intertechne, 2009). An issue reported worldwide, is that even when monitoring programmes 373 are conducted, most of the data obtained are often not published or made available and thus 374 remain inaccessible to further scientific studies ( and is believed to have recently diverged from the endemic species P. hartii (Melo et al, 2018). 397…”
Section: Discussion 322mentioning
confidence: 99%